From Krakow to Krypton : Jews and comic books - Kaplan, Arie. (Philadelphia : Jewish Publication Society, 2008)
Jews created the first comic book, the first graphic novel, the first comic book convention, the first comic book specialty store, and they helped create the underground comics (or "Comix") movement of the late '60s and early '70s. Many of the creators of the most famous comic books, such as Superman, Spiderman, X-Men, and Batman, as well as the founders of MAD magazine, were Jewish. From Krakow to Krypton: Jews and Comic Books tells their stories and demonstrates how they brought a uniquely Jewish perspective to their work and to the comics industry a.
pt. 1. The Golden Age (1933-1955): the birth of the comics. ch. 1. Famous funnies -- ch. 2. Leger and Reuths -- ch. 3. Supergolem -- ch. 4. Attack of the clones -- ch. 5. People of the (comic) book -- ch. 6. The spirit of the times -- ch. 7. The Leaden Age -- ch. 8. Why we fight -- ch. 9. New trends and innocent seducers -- pt. 2. The Silver Age (1956-1978): the growth and development of Jewish comics. ch. 10. Super family values -- ch. 11. Broome makes a clean sweep -- ch. 12. Stan and Jack -- ch. 13. The superhero from Queens -- ch. 14. Courting the college crowd -- ch. 15. Outsider heroes -- ch. 16. Openly Jewish, openly heroic -- ch. 17. Kirby's fourth world -- ch. 18. Notes from the underground -- ch. 19. From novel graphics to graphic novels -- pt. 3. The Bronze Age (1979-the present): comics in the modern world. ch. 20. From comix to graphix -- ch. 21. The Maus that art built -- ch. 22. A graphic approach to Jewish history -- ch. 23. The Martian Jew -- ch. 24. Children of the atom--and Eve -- ch. 25. Vertigo visions -- ch. 26. Up, up, and away--but where to?
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 650
Keywords: Comic books, strips, etc -- United States -- History and criticism; Jewish cartoonists -- United States -- Biography; Jews -- United States -- Intellectual life; COMICS & GRAPHIC NOVELS -- Anthologies; COMICS & GRAPHIC NOVELS -- Contemporary Women; COMICS & GRAPHIC NOVELS -- Crime & Mystery; COMICS & GRAPHIC NOVELS -- Erotica; COMICS & GRAPHIC NOVELS -- Fantasy; COMICS & GRAPHIC NOVELS -- Horror; COMICS & GRAPHIC NOVELS -- Gay & Lesbian; COMICS & GRAPHIC NOVELS -- Historical Fiction; COMICS & GRAPHIC NOVELS -- Literary; Comic books, strips, etc; Jewish cartoonists; Jews -- Intellectual life; United States; Electronic book; Electronic books; Biography; Criticism, interpretation, etc